Policy and priorities for national cancer control planning in low- and middle-income countries: implications of the ASEAN Cost In Oncology Study - Woodward, M; Bhoo-Pathy, N; Yip, C; Peters, S; Kimman, M; Sullivan, R; Jan, S; Ng, C (Elsevier, 2017)
Background We determined the overall and country-specific risk of death and adverse economic outcomes in the ASEAN Costs In Oncology study, and evaluated their contributory factors. Methods 9,513 cancer patients from eight low- and middle-income countries (LMIC) in Southeast Asia were followed-up for 12 months using questionnaires and cost diaries to estimate household-level illness-related expenditures. Overall and country-specific incidence of financial catastrophe (out-of-pocket health costs >=30% of annual household income), economic hardship (inability to make necessary household payments), poverty (living below national poverty line), and death were estimated. Stepwise multinomial regression was used to disentangle the impact of health insurance, cancer stage, and treatment in explaining risk of adverse outcomes. Results A high one-year incidence of mortality (12% in Malaysia to 45% in Myanmar) and financial catastrophe (24% in Thailand to 68% in Vietnam) were observed. Economic hardship was reported by a third of families, including the inability to pay for medicines (45%), mortgages (18%), and utilities (12%), with 28% taking personal loans, and 20% selling assets. Five percent of households were pushed into poverty at one year. Cancer stage largely explained the variations in incidence of financial catastrophe and death in all countries. Stage-stratified analysis however showed that low-income patients remained vulnerable to adverse outcomes even when diagnosed early. Conclusion Apart from high cancer mortality rates in LMIC, many affected households are economically incapacitated within a year of cancer diagnosis. The LMIC need to realign their focus on early detection of cancer and provision of equitable cancer control services.